The partisan politics of employment protection legislation: social democrats, christian democrats, and the conditioning effect of unemployment - Zohlnhöfer, Reimut; Degen, Linda (European political science review, 2021)
Political parties are likely to hold differing views about employment protection legislation (EPL). While pro-welfare parties could support EPL, pro-market parties might focus on labour market deregulation. In this paper, we investigate empirically whether partisan politics, especially the government participation of Social democrats and Christian democrats, matter for EPL in 21 established OECD countries from 1985 to 2019. We show that during the golden age of the welfare state, the level of EPL was much higher where Social and Christian democrats dominated the government than elsewhere. After the golden age and under conditions of high unemployment, these unconditional effects mostly disappeared. Instead, the level of unemployment conditions partisan differences. Christian democrats liberalize EPL for regular employment significantly less than other parties under high levels of unemployment. In contrast, Social democrats defend high levels of EPL for regular and temporary employment when unemployment is low. Against expectations, they even liberalize employment protection for labour market insiders more than other parties at very high levels of unemployment.